1993
DOI: 10.1093/carcin/14.8.1549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea catechins in a rat multi-organ carcinogenesis model

Abstract: The effects of dietary administration of green tea catechins (GTC) were examined using a multi-organ carcinogenesis model. Groups of 15 F344 male rats were initially treated with a single i.p. administration of 100 mg/kg body wt N-diethyl-nitrosamine, 4 i.p. administrations of 20 mg/kg body wt N-methylnitrosourea, 4 s.c. doses of 40 mg/kg body wt 1,2-dimethylhydrazine, together with 0.05% N-butyl-N-(4-hydroxybutyl)nitrosamine for 2 weeks and then 0.1% 2,2'-dihydroxy-di-n-propylnitrosamine for 2 weeks, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…Thus, green tea catechins exerted a significant protective effect against small intestinal cancer but slightly enhanced hepatocarcinogenesis in a dose dependent manner. 107 …”
Section: B Duodenummentioning
confidence: 99%
“…Thus, green tea catechins exerted a significant protective effect against small intestinal cancer but slightly enhanced hepatocarcinogenesis in a dose dependent manner. 107 …”
Section: B Duodenummentioning
confidence: 99%
“…For detecting carcinogenic agents active in other tissues within a relatively short period, we have developed whole-body system models using wide-spectrum initiation by sequential treatment with 3-5 potent carcinogens having different organ spectra of carcinogenicity. Using multiple organ initiator models (medium-term multi-organ models), preliminary results have indicated that most carcinogens can be detected because of increased development of lesions in target organs within 24 or 36 wk (9,14,(22)(23)(24)39). This approach is also receiving international recognition (29).…”
Section: Marker Lesionsmentioning
confidence: 99%
“…1). Green tea catechins were also reported to inhibit small intestinal carcinogenesis but not hepatocarcinogenesis [38]. Such interesting differences probably result from the different distributions of catechins among the organs.…”
Section: Discussionmentioning
confidence: 99%